Ballet Immemorial - Katy Oliver (Journal of Anime and Manga Studies)
In W.J.T. Mitchell’s essay “Metapictures,” Mitchell claims that Diego Velásquez’s painting Las Meninas is “a veritable whirlpool of interpretive ‘aspects,’ switching and alternating the places of painter, beholder, and model, the viewer and the viewed… The figure of the ‘whirlpool’ suggests a way of specifying (or picturing) the multistability effect in a graphic form” (75). Mitchell’s “whirlpool of interactive ‘aspects’” provides an excellent means of grafting the concept of the metapicture onto different artistic discourses—here, ballet and its counterpart, meta-ballet (75). I contend that meta-ballet has two components: it comprises both the deliberate act of referencing the balletic canon and also the process of exploring the constituent parts of the balletic tradition (gesture and bodily movement, staging, performativity, and so on) in a way that mutates normative understandings of ballet. This paper’s aims are twofold: firstly, I develop the concept of meta-ballet and apply it to the show Princess Tutu. Secondly, I explore the uniquely meta-balletic nature of ballet pantomime and bodily motion as deployed by the show. Princess Tutu is quite self-consciously a meta-ballet, making constant references to real-world ballets, ballet techniques, and balletic pantomime. Its playful re-articulations and references to the canonical Western ballets of the nineteenth century illustrate the rich possibilities within ballet’s vast and variegated archive of bodies, texts, performances, and gestures.